Kelas Ibu Hamil dalam Upaya Pencegahan Hipertensi Kehamilan - Nurhidayah Nurhidayah; Hasnah Hasnah; Fauziah Ayu Pratiwi (FORIKES, 2022)
Hypertension in pregnancy is one of the causes of maternal death. So a study is needed to analyze the effect of pregnant women's classes with increased knowledge on the prevention of pregnancy hypertension. The method in this study is a literature review. Database search through PubMed, Science Direct, and Google Scholar. The search results obtained 3200 articles. The articles that were collected were then carried out by an identification process taking into account the suitability of the topic of the literature so that 25 articles were obtained. Screening was carried out so that there were 13 articles left. Oil eligibility check for 10 articles. Based on the results of the review, it is known that there is an effect of implementing classes on pregnant women with increased knowledge on preventing hypertension in pregnancy. Pregnant women will more easily recognize the danger signs of pregnancy such as hypertension that occurs in pregnant women. The class program for pregnant women can be one of the supporting factors for increasing the knowledge of pregnant women about hypertensive disorders in pregnancyKeywords: hypertension in pregnancy; pregnant women class; knowledge ABSTRAK Hipertensi dalam kehamilan merupakan salah satu penyebab kematian ibu. Maka diperlukan studi untuk menganalisis pengaruh kelas ibu hamil dengan peningkatan pengetahuan terhadap pencegahan hipertensi kehamilan. Metode dalam studi ini adalah tinjauan literatur. Penelusuran database melalui PubMed, Science Direct, dan Google Scholar. Hasil pencarian didapatkan 3200 artikel. Artikel yang terkumpul kemudian dilakukan proses identifikasi dengan memperhatikan kesesuaian topik literatur sehingga didapatkan 25 artikel. Screening dilakukan sehingga tersisa 13 artikel. Pemeriksaan eligibility minyasakan 10 artikel. Berdasarkan hasil review, diketahui bahwa ada pengaruh pelaksanaan kelas ibu hamil dengan peningkatan pengetahuan terhadap pencegahan hipertensi kehamilan. Ibu hamil akan lebih mudah mengenali tanda-tanda bahaya kehamilan seperti penyakit hipertensi yang terjadi pada ibu hamil. Program kelas ibu hamil dapat menjadi salah satu faktor pendukung peningkatan pengetahuan ibu hamil mengenai gangguan hipertensi pada kehamilanKata kunci: Hipertensi dalam kehamilan; kelas ibu hamil; pengetahuan